Contribution of the FtsQ Transmembrane Segment to Localization to the Cell Division Site - Scheffers, Dirk-Jan (American Society for Microbiology (ASM), 2007)
The Escherichia coli cell division protein FtsQ is a central component of the divisome. FtsQ is a bitopic membrane protein with a large C-terminal periplasmic domain. In this work we investigated the role of the transmembrane segment (TMS) that anchors FtsQ in the cytoplasmic membrane. A set of TMS mutants was made and analyzed for the ability to complement an ftsQ mutant. Study of the various steps involved in FtsQ biogenesis revealed that one mutant (L29/32R;V38P) failed to functionally insert into the membrane, whereas another mutant (L29/32R) was correctly assembled and interacted with FtsB and FtsL but failed to localize efficiently to the cell division site. Our results indicate that the FtsQ TMS plays a role in FtsQ localization to the division site.